Pelaksanaan Aktivitas Fisik Untuk Meningkatkan Kebugaran Pada Lansia Didesa Sungai Tuan Ulu, Kab Banjar - Nadya Resiana Novianty; Muhammad Said Abdullah; Olga Jadha Casmira (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Partner: The community service partners in this program were elderly individuals in Sungai Tuan Ulu Village.Problem Identification: A common problem experienced by the elderly is a decline in physical fitness due to limitations in performing physical activities outside the home and in daily environments. Physical activity plays a crucial role as body movement produced by skeletal muscles during daily activities, which requires energy expenditure and contributes to improving physical fitness among the elderly. Solution: The implementation of physical activity was conducted using the Global Physical Activity Questionnaire (GPAQ), which emphasizes recalling previously performed physical activities. In addition, physical fitness was measured using the Six-Minute Walking Test (6MWT), aimed at assessing an individual’s fitness level by walking for six minutes on a track of less than 30 meters. Objective: To determine the level of physical fitness among the elderly. Methods: Physical fitness was assessed using the Six-Minute Walking Test, while physical activity levels were evaluated using the Global Physical Activity Questionnaire (GPAQ). Results: The results of this community service program indicate that it can serve as a solution for the elderly to understand the importance of engaging in physical activity to maintain health and physical fitness